2021
DOI: 10.1101/2021.10.08.21264708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of training and workstation adjustability on teleworker discomfort during the COVID-19 pandemic

Abstract: Advancements in telework have increased occupational flexibility for employees and employers alike. However, while effective telework requires planning, the COVID-19 pandemic required many employees to quickly shift to working from home without making sure the requirements for telework were in place beforehand. This study evaluated the transition to telework on university faculty and staff and investigated the effect of telework setup and ergonomics training on work-related discomfort in the at-home environmen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
1
0
2
Order By: Relevance
“…Ainda, em um estudo identificou-se que teletrabalhadores estavam executando seu trabalho no quarto de dormir e na cama, ou na sala de jantar sem mobiliários adequados, ocasionando desconfortos osteomusculares (Larrea-Araujo et al, 2021). Para McAllister et al (2022), a transição para o teletrabalho em trabalhadores de uma universidade trouxe pioras nos desconfortos osteomusculares. Também foi referido nas rodas de conversa que havia diferenças em horários de trabalho, e era comum mensagens de trabalho serem enviadas pelo WhatsApp solicitando respostas rápidas sobre os serviços, enquanto alguns estavam em horário de descanso, gerando preocupações e desgaste.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Ainda, em um estudo identificou-se que teletrabalhadores estavam executando seu trabalho no quarto de dormir e na cama, ou na sala de jantar sem mobiliários adequados, ocasionando desconfortos osteomusculares (Larrea-Araujo et al, 2021). Para McAllister et al (2022), a transição para o teletrabalho em trabalhadores de uma universidade trouxe pioras nos desconfortos osteomusculares. Também foi referido nas rodas de conversa que havia diferenças em horários de trabalho, e era comum mensagens de trabalho serem enviadas pelo WhatsApp solicitando respostas rápidas sobre os serviços, enquanto alguns estavam em horário de descanso, gerando preocupações e desgaste.…”
Section: Resultsunclassified
“…Também surgiram dificuldades com problemas de conexão, interrupções pessoais, e falhas em comunicação além dos problemas de isolamento (Ortiz-Lozano, Martinez-Morán & Férnandez-Munhoz, 2021). Com isso, a mudança forçada para o teletrabalho teve repercussões negativas nos aspectos psicossociais e emocionais, além de repercussões físicas (McAllister et al, 2022).…”
Section: Introductionunclassified
“…15 A number of studies that carried out a quantitative assessment of telework workstations during this period showed that approximately half of the evaluations performed pointed to ergonomic inadequacies in which immediate intervention in the workstation was suggested. [16][17][18] In most of the studies, it was noticed that there was an increase in the prevalence of musculoskeletal problems after adopting telework as a result of the COVID-19 pandemic, although without establishing a direct relationship with the participants' working conditions, 6,7,13,[19][20][21][22][23] whereas some others pointed out that this increase was related to environmental and ergonomics conditions in telework, such as lack of a dedicated place where the workers could concentrate for work. 10,[24][25][26] Ergonomic and environmental suitability of the workplace at home can also be related to a positive view and to the perception of the advantages of telework, as well as to productivity.…”
mentioning
confidence: 99%